2023
DOI: 10.1093/jme/tjad030
|View full text |Cite
|
Sign up to set email alerts
|

Passive collection of ticks in New Hampshire reveals species-specific patterns of distribution and activity

Abstract: Ticks and tick-borne diseases are increasing in the United States, including New Hampshire (NH). We report on the findings of an ongoing free crowdsourcing program spanning four years within NH. The date of tick’s submission was recorded along with species, sex, stage, location they were collected (translated into latitude and longitude), the activity the individual was doing when the tick was found, and host species. A total of 14,252 ticks belonging to subclass Acari, family Ixodidae and genera Ixodes, Derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The study found the highest abundance of I. scapularis concentrated in April to June and September to November. Holistically, the study proposed two high suitability areas in the state, specifically southern and central, and recommended that April to August be considered high risk for humans in New Hampshire to encounter I. scapularis and D. variabilis ticks since this time of the year concentrates the maximum activity of both most prominent tick species [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found the highest abundance of I. scapularis concentrated in April to June and September to November. Holistically, the study proposed two high suitability areas in the state, specifically southern and central, and recommended that April to August be considered high risk for humans in New Hampshire to encounter I. scapularis and D. variabilis ticks since this time of the year concentrates the maximum activity of both most prominent tick species [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at https: //www.mdpi.com/article/10.3390/microorganisms12010050/s1: Table S1: Overview of measured or estimated impacts of determinants on TBDs [7,9,18,27,28,40,43,44,[46][47][48][50][51][52][53]56,57,59,60,63,64,102,103,105,.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…burgdorferi s.s. was highest in the counties with the highest Lyme disease incidence. Recent studies have reported records of I. scapularis from all 10 counites in New Hampshire by 2017, with collections being most common in the southeast and least common to the north ( Eaton, 2023 ; Fernández-Ruiz et al, 2023 ). Regular future tick surveys across New Hampshire are of interest to track the proliferation of I. scapularis in the state.…”
Section: Geographic Distribution Of I Scapularis R...mentioning
confidence: 99%